H-index of geology journals: A statistical analysis based on scimago journal and country ranking. Issue 1 (2nd January 2018) - Renjith, V. R.; Shihab, I.
Abstract : The study is based on geology journals that are covered in the database of SCImago Journal and Country Ranking database for the year 2015. Statistical Package for the Social Sciences (SPSS) is used for statistical computing. This study reveals that there is significant difference between open access and subscription based access journals in geology with regard to h-index. There is also a strong positive correlation among various factors of the journals in geology. It also predicts appropriate regression approach for calculating h-index based on relevant predictor variables. The study is limited by covering journals in geology subject field only from the SCImago Journal and Country Ranking for the year 2015. The valued article contributions in geology subject can be attracted by the journals having high h-index.